2015
DOI: 10.3109/00365521.2014.985705
|View full text |Cite
|
Sign up to set email alerts
|

Role of laparoscopic surgery in the treatment of ulcerative colitis; short- and mid-term results

Abstract: Laparoscopy can be used for ulcerative colitis both emergency and elective cases, it provides a good quality of life and the mid-term rate of complications is lower as compared with open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
11
0
3
Order By: Relevance
“…There was no significant difference in early postoperative complications between robotic and open surgery following IPPA [ 17 ], largely consistent with early meta-analyses of laparoscopic versus open studies during the ascending phase of the laparoscopic learning curve which reported, aside from a lower incidence of wound infection in laparoscopic surgery [ 35 ], equivalent adverse event rates between the 2 groups [ 35 37 ]. More recent studies indicate that laparoscopic surgery is associated with fewer early complications and lower rates of pelvic sepsis [ 39 , 40 ] than open surgery [ 28 , 33 , 38 ]. However, the supplementary use of mini-laparotomies or Pfannenstiel incisions in robotic surgery is often necessary and may limit the benefits that have been seen in other minimally invasive surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in early postoperative complications between robotic and open surgery following IPPA [ 17 ], largely consistent with early meta-analyses of laparoscopic versus open studies during the ascending phase of the laparoscopic learning curve which reported, aside from a lower incidence of wound infection in laparoscopic surgery [ 35 ], equivalent adverse event rates between the 2 groups [ 35 37 ]. More recent studies indicate that laparoscopic surgery is associated with fewer early complications and lower rates of pelvic sepsis [ 39 , 40 ] than open surgery [ 28 , 33 , 38 ]. However, the supplementary use of mini-laparotomies or Pfannenstiel incisions in robotic surgery is often necessary and may limit the benefits that have been seen in other minimally invasive surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…compared with the open technique [8,9] . After successful surgical interventions, quality of life improved continuously, and pouchitis was considered the main problem [4] .…”
Section: Comparing Laparoscopy and Open Surgerymentioning
confidence: 99%
“…Limited data are available on quality of life in patients with UC undergoing surgery. Our working group was the first to publish mid-and long-term results on laparoscopic treatment of UC in Hungary, which proved the success of the method [8,9] .…”
Section: Introductionmentioning
confidence: 96%
“…Magyarországon a CU sebészi kezelésének eredményeit illetően kevés adattal rendelkezünk. Hazánkban elsőként a Szegedi Tudományegyetem Sebészeti Klinikáján dolgozó munkacsoportunk számolt be a CU sebészi kezelésének utánkövetéséről, rövid és hosszú távú eredményeiről és életminőségre gyakorolt hatásáról a laparoszkópos sebészi kezelés vonatkozásában [12][13][14]. A Szegedi Tudományegyetem Sebészeti Klinikáján 2005-ben került bevezetésre a minimálisan invazív technika használata a CU kezelésében, mely módszer intézetünk gyakorlatában évről évre egyre nagyobb teret nyert.…”
unclassified